(untitled) (Research, Society and Development, 2023)
Oral mucositis (OM) is an acute inflammatory disease observed in cancer patients, caused by antineoplastic therapies. Therefore, the present study aimed to verify, in the available literature, the types of treatment, prevention and general characteristics of OM. An integrative literature review was carried out by searching the electronic databases PubMed and Periodicals CAPES. The search strategy was based on the search for the descriptors “oral mucositis”, “child”, “adolescent”. Articles published in English between the years 2017 and 2022 were selected. Thus, the online search resulted in 49 studies selected according to the descriptors used, 20 from the PubMed database and 29 from the CAPES Journal. Of these, 19 articles addressed the theme, considered relevant studies, and included in this literature review. However, this work contributed to identify the different ways of treating OM in patients undergoing chemotherapy and/or radiotherapy, which still does not have a single protocol. Knowledge about the cause of OM, as well as its general characteristics, is of fundamental importance for the development, prevention, and contribution to the general health of children undergoing cancer treatment.